2009
DOI: 10.1097/pas.0b013e3181788533
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Digital Fibroma/Fibromatosis

Abstract: The clinicopathologic and immunohistochemical features of 69 pediatric examples of infantile digital fibroma/fibromatosis (IDF) were analyzed. Thirty males, 26 females, and 1 child (sex unstated) ranging from newborn to 120 months of age (median, 12 mo) manifested 74 lesions (5 identified in follow-up) involving the toe or finger (n=71) and the hand or foot (n=3). Tumors ranged in size from 3 to 35 (median, 10) mm. All but 4 study members presented with a solitary lesion. Metachronous IDFs developed in 7 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(12 citation statements)
references
References 70 publications
(163 reference statements)
0
12
0
Order By: Relevance
“…Studies report that trichrome histochemical staining 4,5,7,8,36 and anti-actin immunostaining 5,7,8,16,37 highlight the often times inconspicuous inclusion. Not restricted to IPM, the hyaline globule is a well-recognized hallmark of another myofibroblastic process, the infantile digital fibroma/fibromatosis 38 , and has also been described in a number of pathologically diverse myofibroblastic and smooth muscle proliferations 39 . The inclusion is believed to result from perturbations in the assemblage of actin filaments within the cytoplasm of myoid cells 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report that trichrome histochemical staining 4,5,7,8,36 and anti-actin immunostaining 5,7,8,16,37 highlight the often times inconspicuous inclusion. Not restricted to IPM, the hyaline globule is a well-recognized hallmark of another myofibroblastic process, the infantile digital fibroma/fibromatosis 38 , and has also been described in a number of pathologically diverse myofibroblastic and smooth muscle proliferations 39 . The inclusion is believed to result from perturbations in the assemblage of actin filaments within the cytoplasm of myoid cells 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Not restricted to IPM, the hyaline globule is a well-recognized hallmark of another myofibroblastic process, the infantile digital fibroma/fibromatosis 38 , and has also been described in a number of pathologically diverse myofibroblastic and smooth muscle proliferations 39 . The inclusion is believed to result from perturbations in the assemblage of actin filaments within the cytoplasm of myoid cells 39 . Michal et al 36 showed ultrastructurally that the fully developed globule in IPM consists of tightly packed actin microfilaments and, like Weiss et al 4 , noted a higher concentration of these inclusions adjacent to the collagenous bodies.…”
Section: Discussionmentioning
confidence: 99%
“…IDF preferentially occurs during early childhood and is present at birth in about 30% of the cases. 1 Predilection sites include the distal phalanx of the fingers and the toes. Initially IDF was considered as a potentially malignant tumor, leading to the amputation of the affected digits.…”
Section: Introductionmentioning
confidence: 99%
“…Initially IDF was considered as a potentially malignant tumor, leading to the amputation of the affected digits. 13 More recently several case reports of spontaneous regression suggest a benign biological behavior. 35 Malignant transformation and metastases have never been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation